Euro Area : Staff Report on the Monetary and Exchange Rate Policies of the Euro Area; Supplement Updating Information on Economic and Financial Developments in the Euro Area; Public Information Notice Following Consultation; Statement by the Executive Director on Monetary and Exchange Rate Policies of the Euro Area. (IMF Staff Country Reports; Country Report, 2001)
A series of adverse supply and demand shocks have brought the euro area's three-year expansion to a virtual standstill. Buoyant labor markets, which have been the hallmark of the recovery since 1997, have succumbed only gradually to the slowing of output growth. The slowdown has been pervasive throughout the area, albeit unevenly and with different cyclical implications. Recent travails notwithstanding, the second half of the 1990s saw a significant improvement in the macroeconomic performance of the euro area.